Immunohistochemical analysis of microglial changes in the experimental acute hepatic encephalopathy - T. V. Shulyatnikova (Zaporozhye State Medical University, 2021)
Hepatic encephalopathy (HE) is a syndrome of impaired brain function in patients with advanced liver failure and it manifests in form of psychometric tests alterations up to decreased consciousness and coma. The current knowledge about HE mainly focused on the theory of ammonia neurotoxicity and neuroinflammation. Microglia being resident innate immune cells of the brain when activated are responsible for the neuroinflammatory reactions. The aim - immunohistochemical study of the microglial changes in different rat brain regions in conditions of experimental acute HE (AHE). Materials and methods. We used acetaminophen induced liver failure model in Wistar rats. Four from 10 animals that survived up to 24 h after acetaminophen injection constituted "compensated group"; 6 animals which died within 24 h - "decompensated group". Microglial reactive changes were analysed by the evaluation of the relative area (S rel., %) of CD68+ expression in the brain cells not associated with meninges and vessels, as well as the changing in shape and number of these cells. Results. Acetaminophen-induced AHE in rats was characterized by the regional- and time-dependent dynamic increase in CD68 expression level in the rat brain in form of significant (relatively to control) increase of CD68+ S rel. in brain cells and the number of such cells. The medians of CD68+ S rel. and their numbers in significantly changed regions of non-survived rats were, respectively: subcortical white matter - 0.24 (0.20; 0.26) and 11.00 (8.00; 13.00); thalamus - 0.13 (0.90; 0.18) and 6.00 (3.00; 7.00); caudate/putamen - 0.13 (0.12; 0.18) and 7.00 (4.00; 11.00) - all indicators were statistically significant compared to control. In the survived animals, indicators were, respectively: subcortical white matter - 0.24 (0.16; 0,26) and 10.00 (8.00; 12.00); caudate/putamen - 0.12 (0.10; 0.15) and 6.00 (4.00; 10.00) - the differences were significant compared to control. Conclusions. The highest and significant indicators were revealed at 24 h (compared to earlier time points) of the experiment in the white matter, thalamus and caudate/putamen. This fact reflects time-dependent dynamic boosting of reactive changes in microglia and presumably may indicate the regions of the most active neuroinflammatory response within the brain parenchyma in the conditions of AHE. The appearing of a small percentage of cells with amoeboid transformation among CD68+-cells may mean partial functional insufficiency of such cells due to probable suppressive impact of ammonia or other influencing factors, as well as insignificance of the material that needs to be phagocytosed under established conditions.